2015
DOI: 10.1111/cid.12373
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Center Prospective, Randomized, Clinical, and Radiographic Study Comparing Osteotome Sinus Floor Elevation with or without Bone Graft and Simultaneous Implant Placement

Abstract: Endo-sinus bone gained after OSFE inevitably and significantly shrinks regardless of whether grafting material is applied or not. Grafting material offers no significant advantage to stability nor clinical success of hydrophilic and nanostructured implants placed simultaneously with OSFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
3
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(89 citation statements)
references
References 34 publications
2
75
3
9
Order By: Relevance
“…But at the same time, two points must be pointed out. First, this conclusion is based on the data of only five clinical trials, the follow‐up time of two trials lasted for only 6 months, only one follow‐up period of the five trials lasted for 5 years (the overall sample size in this study was 37 implants); second, as for the short‐term (<1 year) success rate of the implant, the quality of the evidence has not reached a high level. Therefore, we should be cautious in making clinical decisions.…”
Section: Discussionmentioning
confidence: 94%
“…But at the same time, two points must be pointed out. First, this conclusion is based on the data of only five clinical trials, the follow‐up time of two trials lasted for only 6 months, only one follow‐up period of the five trials lasted for 5 years (the overall sample size in this study was 37 implants); second, as for the short‐term (<1 year) success rate of the implant, the quality of the evidence has not reached a high level. Therefore, we should be cautious in making clinical decisions.…”
Section: Discussionmentioning
confidence: 94%
“…Two studies were excluded because the same patient cohort was used . Finally, 7 studies were included in this review (Fig ) . Table shows the general characteristics of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…All seven studies compared the implant survival rates after OSFE with and without grafting (Table ). Nedir et al and Markovic et al used the success criteria of Buser et al (1997), and Si et al used the success criteria of Buser et al (1997) and Cochran et al (2002) to describe clinical implant survival. The random‐effect model meta‐analysis based on 463 implants in patients without grafting and 415 implants in patients with grafting showed that the risk ratio difference of survival rates was 1.010 (95%CI 0.910, 1.120), which did not reach statistical significance ( P = 0.99) (Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, at 12 months post‐surgery aGH was 0 in 13% of patients of the tSFE group. Although there is substantial agreement on the fact that the space augmented with a sinus floor elevation procedure undergoes progressive reduction over time (Abdulkarim, Miley, McLeod, & Garcia, ; Brägger et al, ; Jung, Choi, Cho, & Kim, ; Mardinger et al, ; Marković et al, ; Mazzocco et al, ; Nishida et al, ; Pjetursson et al, ; Tallarico et al, ; Temmerman et al, ; Umanjec‐Korac, Wu, Hassan, Liu, & Wismeijer, ), the relevance of the presence and extent of a grafted volume beyond the implant surface and its progressive remodeling for the long‐term implant prognosis is currently unknown. Long‐term follow‐up of the treated cases will allow for clarifying further the relevance of aGH for implant prognosis following sinus floor elevation.…”
Section: Discussionmentioning
confidence: 99%